The potential of a method for the synthesis of ceramic-cementitious materials processed by an alternative route - Martínez-Vásquez, J. D.; Ortega-Zavala, D. E.; Vargas Gutiérrez, G.; Fuentes, A. F.; Escalante-García, J. I. (Revista ALCONPAT, 2015)
Formulations of thermochemically bonded ceramics based on silicoaluminate raw materials werecharacterized. The mixtures were prepared using low water:solid and these were pressed under up to30MPa. The specimens were cured for 2 hours at 200°C and were further characterized. The flexuralstrength registered 6.9-15.7 MPa, which was higher than common cements conventionally processed. Themicrostructures were dense, suggesting a favorable response of the mixtures to the activation process. Theflexural strength varied with the type and amount of mixed raw materials. X-ray diffraction indicated thatthe crystalline phases from the raw materials did not react; the formation of zeolites was not observed.The proposed processing is promising in order to obtain high strength in short curing times.Keywords: geopolymers; ceramics chemically bound; activated clays; precast products